The Effect of an Oxytocin Rest Period on Cesarean Delivery Blood Loss [35P]. (May 2020) - Cochrane, Elizabeth; Huber, Ashley; Jou, Christopher; Chappelle, Joseph
Abstract : INTRODUCTION: Studies have demonstrated that two hours of oxytocin exposure can desensitize uterine oxytocin receptors; which may increase blood loss during delivery. Oxytocin's half-life is 10–15 minutes, previous work suggests that it takes approximately 60 minutes to be eliminated. Our objective was to determine if a greater than 60-minute oxytocin rest period prior to cesarean delivery had an impact on blood loss. METHODS: An IRB-approved retrospective cohort study of 272 women who underwent primary cesarean delivery after oxytocin augmentation between January 2013 and December 2017 at Stony Brook University Hospital was conducted. Women with a prior cesarean delivery, a cesarean hysterectomy, multiple gestation, and a greater than 240 minute oxytocin rest period were excluded. The primary outcome was percentage change between pre- and post-operative hematocrit (Hct) in women with less than 60-minute oxytocin rest period (60 min). RESULTS: There was no difference in demographic or obstetric characteristics between the groups. Women in the >60 min group had a higher cumulative dose (5112+4765 mU vs. 77017325 mU, P= .003), longer duration of oxytocin administration (671±458 min vs. 892±558 min, P= .001), and were more likely to receive uterotonics (6.7% vs. 15.2%, P= .047). No significant difference in percent change in HCT (-17.3±8.6 vs. -17.8±8.7, P= .635) was identified. Linear regression demonstrated a weak relationship between cervical dilation and percent change in Hct. (R 2 =0.048, P<.001). CONCLUSION: No significant correlation between duration of oxytocin rest period and blood loss was found. Women receiving oxytocin augmentation do not appear to benefit from oxytocin rest periods before proceeding to cesarean delivery.